Cognitive disabilities and web accessibility: a survey into the Brazilian web development community - Talita Cristina Pagani Britto Pichiliani; Ednaldo Brigante Pizzolato (Journal on Interactive Systems)
Cognitive disabilities include a diversity of conditions related to cognitive functions, such as reading, understanding, learning, solving problems, memorization and speaking. They differ largely from each other, making them a heterogeneous complex set of disabilities. Although the awareness about cognitive disabilities has been increasing in the last few years, it is still less than necessary compared to other disabilities. The need for an investigation about this issue is part of the agenda of the Challenge 2 (Accessibility and Digital Inclusion) from GranDIHC-Br. This paper describes the results of an online exploratory survey conducted with 105 web development professionals from different sectors to understand their knowledge and barriers regarding accessibility for people with cognitive disabilities. The results evidenced three biases that potentially prevent those professionals from approaching cogni-tive disabilities: strong organizational barriers; difficulty to understand user needs related to cognitive disabilities; a knowledge gap about web accessibility principles and guidelines. Our results confirmed that web development professionals are unaware about cognitive disabilities mostly by a lack of knowledge about them, even if they understand web accessibility in a technical level. Therefore, we suggest that applied research studies focus on how to fill this knowledge gap before providing tools, artifacts or frameworks.